2010
DOI: 10.1007/s12666-010-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the coating technique on the high cycle fatigue life of alumina coated Al 6061 alloy

Abstract: The primary objective of this study is to evaluate the influence of coating technique on the high cycle fatigue of an Al6061 alloy. Towards this purpose, Al6061 alloy fatigue samples have been coated with Al 2 O 3 utilising the detonation spray, air plasma spray, micro arc oxidation and hard anodizing techniques. The high cycle fatigue life of these coated samples has been evaluated over a range of alternating stress values and compared with the fatigue life of the uncoated Al6061 alloy. It is observed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…As a result, the coating is very well bonded to the substrate, and this should allow the easy propagation of the crack from the coating into the substrate, as discussed in an earlier publication. [32] In addition, it is also clear from Figure 11 that the thick-MAO-coated sample is characterized by a long and thin crack in the coating that has the ability to propagate into the substrate due to the high stress intensity at the tip of such a crack. In contrast, the presence of extensive porosity (Figure 3) in conjunction with the tensile residual stress in the thin MAO coating (Table III) causes multiple cracking in the coating during the fatigue test.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, the coating is very well bonded to the substrate, and this should allow the easy propagation of the crack from the coating into the substrate, as discussed in an earlier publication. [32] In addition, it is also clear from Figure 11 that the thick-MAO-coated sample is characterized by a long and thin crack in the coating that has the ability to propagate into the substrate due to the high stress intensity at the tip of such a crack. In contrast, the presence of extensive porosity (Figure 3) in conjunction with the tensile residual stress in the thin MAO coating (Table III) causes multiple cracking in the coating during the fatigue test.…”
Section: Discussionmentioning
confidence: 98%
“…With increasing of holding time, the depth of corrosion pits becomes bigger and bigger so that the fatigue crack initiation life of aluminum alloy becomes shorter [9]. Most researchers have previously reported fatigue data of aluminum alloys under pre-corrosion mode based on the equivalent life concept according to airplane structure subjected to two main factors of environment corrosion and fatigue loading [9,[23][24][25]. These results indicated that the differences between the cyclic stress corrosion and prior-corrosion HCF damage behaviors of aluminum alloys are always existent.…”
Section: Fatigue Life Characteristicsmentioning
confidence: 99%
“…However, the applications including landing gear components of aerospace sector often demand an additional property namely the fatigue resistance . The current state‐of‐art can only provide adequate wear and corrosion protection of Al alloys even when the advanced technologies such as micro arc oxidation (MAO) are deployed thereby leaving a clear space for developing the materials and processes that can simultaneously provide resistance against wear, corrosion and fatigue …”
Section: Introductionmentioning
confidence: 99%